Anterolateral Thigh Flap—the Optimal Flap in Coverage of Severe Elbow Injuries - Koteswara Rao Rayidi, Venkata; Prakash, Panagatla; Srikanth, R; Sreenivas, Jammula; Swathi, Karavattula (Indian Journal of Plastic Surgery, 2019)
Introduction Traditionally, the latissimus dorsi muscle with or without skin paddle has been the flap of choice for coverage of elbow defects. The ALT flap has found application in elective upper limb defects on account of it’s ability to be tailor made for individual defects. Our series of 10 cases shows the advantages of using this flap for acute trauma defects.Materials and Methods Consecutive 10 cases of severe elbow injuries, involving varying amounts of the lower arm and proximal forearm underwent debridement followed by coverage using the free anterolateral thigh flap. Nine of 10 arterial anastomosis were done end to side to the brachial artery and venous anastomosis to the veins accompanying the artery. Seven of these patients had long bone fractures and elbow dislocations, stabilised using external fixator. Four patients needed primary muscle or tendon repair and nerve repair or graft.Results There was 1 total flap loss, intraoperatively where a TFL flap had been used in a 71 year-old patient. Nine of 10 had successful wound coverage. Using Jupiter criteria, 2 had excellent, 3 had good, 3 had fair, and 1 had poor outcome.Conclusion This consecutive series of moderate and severe elbow injuries demonstrates that the ALT flap should be considered as the flap of first choice, specifically when there is a need.
Keywords: anterolateral thigh flap; elbow injuries; acute trauma